PENGARUH STRUKTUR KEPEMILIKAN, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN MANAJEMEN RESIKO - Saputro, Candra Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This research is conducted to find out the influence of ownership structures, leverage, and company size to the risk management disclosure.The samples are manufacturing companies which are listed in the Indonesia Stock Exchange in the years of 2010 â 2012. The research samples are 9 manufacturing companies which are the rating winners of The Indonesia Most Trusted Company â Corporate Governance Perception Index (IMTC â CGPI). The data analysis is carried out by using SPSS version 20.0 which is preceded by classic assumption tests which consist of normality test, multicolinearity test, heteroscedasticity test and autocorrelation test. The hypothesis test is performed by using F test and t test.The result of this analysis states that simultaneously the ownership structures, leverage, and company size have no influence to the risk management disclosure. Partially, variables of ownership structures, leverage, and company size also state that these variables have no influence to the risk management disclosure.Keywords: Risk Management Disclosure, Ownership Structures, Leverage, and Company Size.